Beyond the surface: a review of transcranial temporal interference stimulation for deep brain modulation - Ivanov, Boyan; Toth, Jake E.; Mandali, Alekhya; Salvati, Roberto; Arvaneh, Mahnaz (Frontiers in Neurology, 2025)
Temporal Interference (TI) stimulation has emerged as a novel, non-invasive technique for selectively modulating deep brain regions while minimizing stimulation of superficial cortical layers, addressing key limitations of traditional transcranial electrical stimulation (tES) methods. This review systematically examines advancements in TI research from June 2017 to December 2024, encompassing safety evaluations, computational modeling (including Finite Element Method simulations), and stimulation–parameter optimisation. The paper synthesizes 63 publications on the efficacy of TI in deep brain neuromodulation, its optimisation strategies, and emerging methodologies aimed at improving stimulation precision and reducing off-target effects. Furthermore, the review explores the clinical applications of TI, particularly its potential in treating neurological disorders such as epilepsy, Parkinson's disease, and cognitive impairments. Despite its promise, challenges remain, including variability in stimulation outcomes, the need for individualized treatment protocols, and gaps in understanding the long-term effects of TI. By consolidating current knowledge and identifying future research priorities, this review provides a comprehensive perspective on the transformative potential of TI stimulation in neuroscience and clinical neurotherapeutics.